Global, regional, and national trends - von Grebmer, Klaus; Bernstein, Jill; de Waal, Alex; Prasai, Nilam; Yin, Sandra; Yohannes, Yisehac (Welthungerhilfe, 2015)
Since 2000, significant progress has been made in the fight against hunger.1 The 2000 Global Hunger Index (GHI) score was 29.9 for the developing world, while the 2015 GHI score stands at 21.7, representing a reduction of 27 percent (Figure 2.1).2 To put this in context, the higher the GHI score, the higher the level of hunger. Scores between 20.0 and 34.9 points are considered serious. Thus while the GHI scores for the developing world—also referred to as the global GHI scores—for 2000 and 2015 are both in the serious category, the earlier score was closer to being categorized as alarming, while the later score is closer to the moderate category. As described in Chapter 1, all GHI calculations in this report, including those for the reference years 1990, 1995, 2000, and 2005, have been calculated using a revised formula. The severity scale was adjusted to reflect this change.